APLIKASI GAME MEWARNAI DENGAN MACROMEDIA FLASH 8 - Ochi Andi Sasongko; Melani Dewi Lusita (Jurnal Sistem Informasi, 2010)
Scientific writing is about the making of Game edutaintment.yang intended forchildren age play group, kindergarten and elementary school children in grade 1,many included images that allows users colored objects in coloredgambar.Game consists of two core components. The first component is thechoice of colors, usually displayed with the color blocks and objects whichbecome targets coloring and added sound notification on every color. Incompleting this writing, the author approached by reading books, articles andbrowse the Internet to get as much information so it can be used to solve theproblem in this writing.